2020
DOI: 10.1088/1674-4926/41/11/111407
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities toward fully automated analog layout design

Abstract: Realizing the layouts of analog/mixed-signal (AMS) integrated circuits (ICs) is a complicated task due to the high design flexibility and sensitive circuit performance. Compared with the advancements of digital IC layout automation, analog IC layout design is still heavily manual, which leads to a more time-consuming and error-prone process. In recent years, significant progress has been made in automated analog layout design with emerging of several open-source frameworks. This paper firstly reviews the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 64 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Recent years have shown that the demand for analog integrated circuits (ICs) increased. In comparison to its digital counterpart, the design flow is rather time-consuming and error-prone, since it is mainly done manually [1]. Therefore, electronic design automation (EDA) tools focused on the analog part are necessary to accelerate the process and reduce the demand for human experts.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have shown that the demand for analog integrated circuits (ICs) increased. In comparison to its digital counterpart, the design flow is rather time-consuming and error-prone, since it is mainly done manually [1]. Therefore, electronic design automation (EDA) tools focused on the analog part are necessary to accelerate the process and reduce the demand for human experts.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that machine-learning-based methods have significantly surpassed traditional approaches in terms of both speed and accuracy [ 15 ]. However, these studies on intelligent circuit design face challenges due to insufficient training datasets.…”
Section: Introductionmentioning
confidence: 99%